TREATMENT OF RESIDUAL TUMORS OF THE TESTIS - A. Sakalo (Bogomolets National Medical University, 2015)
Summary. After chemotherapy (ChT) in seminoma patients the residual tumors (RT) of different size and composition could occur. Either ChT or radiotherapy, active surveillance or surgical excision can be administered in this scenario. We present results in 31 patients with RT, and analysis of factors affecting progression. Statistical work out includes logistic regression and Kaplan-Meier analysis. We found that RT sized > 3 cm are more frequently being diagnosed after ChT of disseminated seminoma. When disease progresses (despite salvagetherapy and surgical excision) the prognosis is worse compared to other patients. When alive tumor is found in RT after ChT of second line the prognosis is worse compared to necrosis or fibrosis in the RT. Stage at the beginning of the treatment and spontaneous regression (stabilization of the process) during the follow up are factors confounding the progression. Surgical treatment of RT is technically complicated and associated with high risk of intraoperative complications. Radiotherapy of RT does not improve survival. Long term follow up and active surveillance during many years is justified due to fact of long lasting regression (stabilization) of the RT.